2006
DOI: 10.1101/lm.148706
|View full text |Cite
|
Sign up to set email alerts
|

Fos and Egr1 expression in the rat brain in response to olfactory cue after taste-potentiated odor aversion retrieval

Abstract: When an odor is paired with a delayed illness, rats acquire a relatively weak odor aversion. In contrast, rats develop a strong aversion to an olfactory cue paired with delayed illness if it is presented simultaneously with a gustatory cue. Such a conditioning effect has been referred to as taste-potentiated odor aversion learning (TPOA). TPOA is an interesting model for studying neural mechanisms of plasticity because of its robustness and rapid acquisition. However, the neural substrate involved in TPOA retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 54 publications
(82 reference statements)
0
21
0
Order By: Relevance
“…According to the alimentary status of animals, mitral cells of OB present increased activity in response to an odor associated to toxicosis (Pager and Royet, 1976). Fos immunoreactivity in PC increased during the retrieval of taste potentiated odor aversion (TPOA) (Dardou et al, 2006(Dardou et al, , 2007. Our data show that COA learning clearly modified odor-induced oscillatory activity in these structures.…”
Section: An Effective Cs-us Association Duringmentioning
confidence: 50%
“…According to the alimentary status of animals, mitral cells of OB present increased activity in response to an odor associated to toxicosis (Pager and Royet, 1976). Fos immunoreactivity in PC increased during the retrieval of taste potentiated odor aversion (TPOA) (Dardou et al, 2006(Dardou et al, , 2007. Our data show that COA learning clearly modified odor-induced oscillatory activity in these structures.…”
Section: An Effective Cs-us Association Duringmentioning
confidence: 50%
“…They showed activation of the basolateral, but not central and medial, parts of the amygdala as measured by c-Fos expression and activation of none of the above-mentioned nuclei as measured with Zif268 expression. Moreover, Dardou et al (84) showed increased level of c-Fos and Zif268 expression in the basolateral amygdala following taste-potentiated odor aversion retrieval; however, in the same test in the central amygdala, they observed no changes in the c-Fos expression and the elevated level of Zif268 expression. Also our results presented on the Figure 9 clearly show discrepant patterns of c-Fos and Zif268 expression in the amygdala following appetitive conditioning.…”
Section: K Comparison Of C-fos Versus Zif268 Expression Patterns Folmentioning
confidence: 96%
“…Indeed, food-paired CSs can activate the gustatory region of the insular cortex (GC) in both rodents (Dardou et al 2006(Dardou et al , 2007 and humans (Veldhuizen et al 2007;Small et al 2008). Importantly, these CSs activate the very same neuronal ensembles in the GC that were activated by the food US itself, providing a neural substrate of CS retrieval of a reward representation (Saddoris et al 2009).…”
Section: Circuitry Of Outcome Representationsmentioning
confidence: 99%